Zola, el naturalismo y la identidad nacional en tres dramas de Florencio Sánchez - Rubio, Francisco García (Latin American Theatre Review, 2010)
This article studies three plays by Florencio Sánchez, La gringa (1904), La pobre gente (1904) and Barranca abajo (1905), in which the presence of Naturalist themes, mainly that of atavistic degeneration, carries this theatre beyond simple awareness of social ills to a direct engagement with the most pressing issues of socio-economic structure and national identity present in Argentinean society at the turn of the century. I first consider Emile Zola’s proposals for a Naturalist theatre as reflected in these plays through the themes of atavistic degeneration and hereditary and environmental determinism. In the second part, I analyze Sánchez’ ideological use of these elements as an attempt at working through the complex set of problems facing the young nation of Argentina in a time of economic and identitary transition. Sánchez put his theatre at the service of social change, following Zola’s proposals. He used theatre to transform a society that inherited the social problems of industrialization of late-nineteenth-century Europe while facing the implications of large-scale immigration for the ideological field of Argentinean national identity. (FGR, Article in Spanish)